S14-4: Equality in Sport and Male Allyship (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Male allyship in Ireland is gaining increased academic and socio-political attention, emerging as a critical component in advancing gender equality. Within a historical context of Catholic conservatism and entrenched patriarchal norms, male allyship challenges traditional gender roles and facilitates a reconfiguration of masculinities. Recent developments – such as the referenda on same-sex marriage (2015) and abortion rights (2018) – have created a new landscape for male allies to work alongside feminist advocates in the pursuit of gender equality. It is acknowledged that real change is contingent on gender transformative approaches that address more entrenched structural inequalities. As the first country in the world to publish the national men’s health policy, Ireland has been to the forefront in promoting healthy masculinities as part of a wider conceptualisation of men’s health and a commitment to gender equality. Civil society organisations and national campaigns (e.g. White Ribbon Ireland) have also played key roles in fostering male engagement with issues such as consent and domestic violence, as well as providing an alternative discourse to toxic masculinity.Description: This session will offer some critical reflections on the potential implications of these initiatives for women in sport. It will consider how sport (including sporting structures and institutions) can be a catalyst for developing and reproducing gender stereotypes such as that boys ‘have to be good’ and girls are ‘no good’ at sport (Women in Sport, 2024, March; Women in Sport, 2024, March 25). Notably, this is against a backdrop of increased online abuse of sportswomen (Women in Sport, 2024, March 25). It will reflect on the invisibility of male privilege in sport and will review the factors underpinning the persistent male bias in the coverage of sport. Conclusions: Drawing upon some key learning within an Irish context, it will offer some suggestions as to how male allyship needs to be framed and conceptualised within a context of greater equality in sport being better for all. It will demonstrate how male allyship demands both cultural transformation and policy-driven change, and that it is a dynamic and often uncomfortable process of reflexively examining male privilege and being accountable. It will conclude by stressing that male engagement in allyship needs to move beyond rhetoric into meaningful and sustained action.